(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Global Food habit is changing with change in life style for the last few decades. This change may be due to many factors like liberalization, dual family income, nuclear family, modern kitchen, time constraints and various other factors. The individuals and population is shifting for their food from fresh agri-product to processed food. This has given a new business opportunity with social uplift, various changes can be observed through the records available on food intake pattern. This study refers the status of food processing industry in central Indian population especially in Chhattisgarh state. Also highlight the techniques of processing the foods to make it consumable in easiest form for the consumers.